From Dirt Roads to Rail Roads to Interstates - Wooldridge, Connie Nordhielm (USA, 2011)
A firsthand account to tell a ''just fine and accurate story of how dirt roads of the 1800s turned into the U.S. Highway system of today...
Keywords: History; Juvenile Non-Fiction; USA